NFAT5/TonEBP limits pulmonary vascular resistance in the hypoxic lung by controlling mitochondrial reactive oxygen species generation in arterial smooth muscle cells - Laban, Hebatullah; Siegmund, Sophia; Zappe, Maren; Trogisch, Felix; Heineke, Jörg; Torre, Carolina de la; Fisslthaler, Beate; Arnold, Caroline; Lauryn, Jonathan; Büttner, Michael; Mogler, Carolin; Kato, Katsuhiro; et al. (Cells, 2021)
Chronic hypoxia increases the resistance of pulmonary arteries by stimulating their contraction and augmenting their coverage by smooth muscle cells (SMCs). While these responses require adjustment of the vascular SMC transcriptome, regulatory elements are not well defined in this context. Here, we explored the functional role of the transcription factor nuclear factor of activated T-cells 5 (NFAT5/TonEBP) in the hypoxic lung. Regulatory functions of NFAT5 were investigated in cultured artery SMCs and lungs from control (Nfat5fl/fl) and SMC-specific Nfat5-deficient (Nfat5(SMC)−/−) mice. Exposure to hypoxia promoted the expression of genes associated with metabolism and mitochondrial oxidative phosphorylation (OXPHOS) in Nfat5(SMC)−/− versus Nfat5fl/fl lungs. In vitro, hypoxia-exposed Nfat5-deficient pulmonary artery SMCs elevated the level of OXPHOS-related transcripts, mitochondrial respiration, and production of reactive oxygen species (ROS). Right ventricular functions were impaired while pulmonary right ventricular systolic pressure (RVSP) was amplified in hypoxia-exposed Nfat5(SMC)−/− versus Nfat5fl/fl mice. Scavenging of mitochondrial ROS normalized the raise in RVSP. Our findings suggest a critical role for NFAT5 as a suppressor of OXPHOS-associated gene expression, mitochondrial respiration, and ROS production in pulmonary artery SMCs that is vital to limit ROS-dependent arterial resistance in a hypoxic environment.